The overtraining syndrome - Lee, J.
It has been reported numerous times that rest or greatly reduced training is necessary for recovery from staleness. In a study conducted by Hooper et al. (1995), tapering did not appear to provide the stale swimmers with sufficient time for complete recovery prior to competition, because fatigue and muscle soreness ratings for the week before taper and post-competition testing were significantly higher for the stale swimmers than for the non stale swimmers. The difficulty of delineating normal from abnormal physiological responses to training presents another problem for investigators, particularly when changes in physiological measures are in the same direction as expected with training (Hooper & Mackinnon, 1995). Since the daily ratings of fatigue during the recovery period of tapering also predicted competitive performance improvement from previous best times, this research suggests that daily logs of training and measures of well-being, completed by the athletes can assist in programming appropriate training loads during intense training and tapering (Hooper et al. 1995). A number of parameters of overtraining are claimed to be identified, but the data are frequently less based on well-founded experimental findings than on experience or individual observations (Urhausen et al. 1995). While many acute changes have been observed following a period of over-reaching (Lehmann et al. 1992; Fry et al. 1992), the data presented demonstrates that those athletes who were suffering from the prolonged effects of the overtraining syndrome had a normal profile for the majority of parameters considered (Rowbottom et al. 1995). This indicated the debilitating fatigue experienced by the overtrained suffers was not related to many of the factors traditionally associated with over-exercise such as low hemoglobin and ferritin concentrations, elevated uric acid, creatine phosophokinase and cortisol concentrations, since levels were normal in overtrained subjects (Rowbottom et al. 1995). Rowbottom concluded that the debilitating fatigue experienced by the overtrained sufferers was not related to any of the blood parameters traditionally associated with over exercise, with the exception of plasma glutamine concentration, and such as glutamine concentration may represent an effective diagnostic criterion for the overtrained syndrome in the future. Fry et al. (1992) cites a decrease in the level of performance and training fatigue from overtraining fatigue must be distinguished for a critical diagnosis of overtraining. Snyder et al. (1995) cites five criteria in diagnosing overtraining, because no single set of symptoms have been found to be associated with overtraining; however, these five criteria represent those symptoms most observed. Unfortunately these criteria provided by Snyder provide no help to the coach unless a laboratory is available (See page 2). Fry et al. (1992) raise the question as to whether or not a statistically significant decrement in performance is required prior to the possibility of diagnosing an overtrained state. It may therefore be recommended that, rather than analyzing results as a group for the detection of performance decrements, it may be more appropriate to compare a subject's individual performance with his/her own previous scores and to diagnose the athlete as overtrained (Fry et al. 1992). Any decrease in the level of performance may or may not be associated with biochemical, haematological, physiological and immunological indications. An outstanding factor to emerge from this research was the difficulty associated with the objective diagnosis of overtraining and this is a possible reason why there are few accounts of overtraining research in the literature. Individual cases may present a different range of symptoms and an overtraining diagnosis should not be excluded based on the failure of blood parameters or any other parameter to demonstrate variation. The simple fact is that we must learn about the quantitative relationship between training and performance on an individual (athlete) basis because of the interrelationships between the variables associated with overtraining seem to be quite variable.